Education of migrant child laborers in hidalgo state: Education process in the current social context - Medecigo Shej, Graciela Amira (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Linking education and child labor s an alternative to improve the training processes of contemporary teachers. This current challenge demands the concentration of efforts on the part of the different actors involved, who must collaborate in the design of new comprehensive and well-founded strategies that, in the long term, contribute to the eradication of the problem. The context experiences within the state of Hidalgo Mexico, expose how the convergence of different variables can result in a significant decrease in child labor in this context.